C1'-Branched acyclic nucleoside phosphonates mimicking adenosine monophosphate: Potent inhibitors of Trypanosoma brucei adenine phosphoribosyltransferase - Kalčic, Filip; Frydrych, Jan; Doleželová, Eva; Slapničková, Martina; Pachl, Petr; Slavětínská, Lenka Poštová; Dračínský, Martin; Hocková, Dana; Zíková, Alena; Janeba, Zlatko (European journal of medicinal chemistry, 2021)
Some pathogens, including parasites of the genus Trypanosoma causing Human and Animal African Trypanosomiases, cannot synthesize purines de novo and they entirely rely on the purine salvage pathway (PSP) for their nucleotide generation. Thus, their PSP enzymes are considered as promising drug targets, sparsely explored so far. Recently, a significant role of acyclic nucleoside phosphonates (ANPs) as inhibitors of key enzymes of PSP, namely of 6-oxopurine phosphoribosyltransferases (PRTs), has been discovered. Herein, we designed and synthesized two series of new ANPs branched at the C1' position as mimics of adenosine monophosphate. The novel ANPs efficaciously inhibited Trypanosoma brucei adenine PRT (TbrAPRT1) activity in vitro and it was shown that the configuration on the C1' chiral centre strongly influenced their activity: the (R)-enantiomers proved to be more potent compared to the (S)-enantiomers. Two ANPs, with Ki values of 0.39 μM and 0.57 μM, represent the most potent TbrAPRT1 inhibitors reported to date and they are an important tool to further study purine metabolism in various parasites.
Keywords: Trypanosomiasis; Dose-Response Relationship, Drug; adenosinmonofosfát; vztah mezi dávkou a účinkem léčiva; Purine salvage pathway; APRT; inhibitory enzymů; Antiprotozoal Agents; Adenosine Monophosphate; Nucleotide analogues; parazitické testy citlivosti; Parasitic Sensitivity Tests; Nucleosides; vztahy mezi strukturou a aktivitou; nukleosidy; Enzyme inhibitors; Trypanosoma brucei brucei; antiprotozoální látky; molekulární struktura; Phosphonates; Structure-Activity Relationship; adeninfosforibosyltransferasa; Adenine Phosphoribosyltransferase; Enzyme Inhibitors; Molecular Structure